ROTATION OF SYSTEM OF N CONNECTED SPHERICAL GRAINS TRIGGERED BY NON- UNIFORM GROWTH OF THE SUB-SYSTEMS AS A MODEL OF FETAL ROTATION - NURHIA DEWI (NIM : 10214019), SINTA
Growth and mechanical properties of fetal in uterus is a complex system. During the prenatal period, the fetal undergoes rotation, changes in size, shape, and mass due to the growth of new organs. A complex system is simplified into two and three connected spherical grains, where each grains, i.e. the sub-systems, could grow with different rate, which introduces non-uniform change in size and mass distribution. Rotation around system center of mass is expected due to this change. Considered forces are binding force (in the term of spring force), buoyant force, gravitational force, and viscous force. This system is modeled analytically and numerically by molecular dynamics use dimensional data obtained from the literature. The numerical model shows a change in the orientation of the object at each time that describes a change in the direction of fetal orientation at each time so that at 36 weeks of gestation the fetal head down position.